Iron nanoparticle bio-interactions evaluated in Xenopus laevis embryos, a model for studying the safety of ingested nanoparticles. Issue 2 (7th February 2020) - Bonfanti, Patrizia; Colombo, Anita; Saibene, Melissa; Fiandra, Luisa; Armenia, Ilaria; Gamberoni, Federica; Gornati, Rosalba; Bernardini, Giovanni; Mantecca, Paride
Abstract: Iron nanoparticles (NPs) have been proposed as a tool in very different fields such as environmental remediation and biomedical applications, including food fortification against iron deficiency, even if there is still concern about their safety. Here, we propose Xenopus laevis embryos as a suitable model to investigate the toxicity and the bio-interactions at the intestinal barrier of Fe3 O4 and zerovalent iron (ZVI) NPs compared to Fe(II) and (III) salts in the 5 to 100 mg Fe/L concentration range using the Frog Embryo Teratogenesis Assay in Xenopus (FETAX). Our results demonstrated that, at concentrations at which iron salts induce adverse effects, both iron NPs do not cause acute toxicity or teratogenicity even if they accumulate massively in the embryo gut. Prussian blue staining, confocal and electron microscopy allowed mapping of iron NPs in enterocytes, along the paracellular spaces and at the level of the basement membrane of a well-preserved intestinal epithelium. Furthermore, the high bioaccumulation factor and the increase in embryo length after exposure to iron NPs suggest greater iron intake, an essential element for organisms. Together, these results improve the knowledge on the safety of orally ingested iron NPs and their interaction with the intestinal barrier, useful for defining the potential risks associated with their use in food/feed fortification.